(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
Bromadiolone is an active ingredient of many newer rodenticides available in the market, for the reason that it is highly fatal for rodent species. Because of its easy availability, it is becoming the poison of choice for committing suicide. Bromadiolone inhibits vitamin K (1)- 2,3 epoxide reductase and thus the synthesis of vitamin K and subsequently clotting factors II, VII, IX and X. Herein, we present a case of fatal suicidal ingestion of bromadiolone rodenticide bait by a young adult woman.